An analysis of service accessibility for diabetes risk groups in community primary health centers, Loei Province - Sathaporn, Sathaporn (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
Diabetes is a significant public health problem with increasing prevalence in Thailand. This cross-sectional analytical study aimed to analyze service accessibility among diabetes risk groups in Community Primary Health Centers in Loei Province. The study examined accessibility situations, influencing factors, barriers and limitations, and proposed service improvement guidelines. The study population consisted of 25,982 individuals at risk of diabetes from 142 community health centers in Loei Province during fiscal year 2568 (October 1, 2024 - September 30, 2025). Data were collected from secondary databases including patient registries and health service databases through approved access procedures. Descriptive statistics and logistic regression analysis were used for data analysis. Results revealed that 81.11% of the risk group accessed screening services, primarily through village health volunteer appointments (84.72%). Factors significantly influencing service accessibility included education level (OR=8.54), distance less than 5 kilometers (OR=3.50), age 55 years or older (OR=0.16), convenient transportation (OR=1.37), adequate personnel (OR=1.33), and service hours (OR=1.25). Major barriers from the user perspective included long distance (46.08%), work obligations (41.92%), and insufficient personnel (43.34%). From the provider perspective, limitations included excessive workload (11 of 15 providers), limited budget (all 15 providers), and outdated equipment (15 of 15 providers). In conclusion, although the majority (81.11%) of the diabetes risk group accessed screening services, approximately 18.89% (which exceeds the national target of 10% non-accessibility) still lacked access. Service development should focus on expanding mobile outreach services, increasing resources, developing integrated data systems, and promoting community participation to ensure comprehensive and efficient service accessibility for diabetes risk groups. Further qualitative research is recommended to understand barriers in depth and conduct long-term follow-up studies on service accessibility outcomes.